Takhrij and Syarah Hadiths of Agrotechnology: Ingredients and Benefits of Aloe Vera - Wina Juwita Febriani; Wahyudin Darmalaksana; Amalia Purdianty (UIN Sunan Gunung Djati Bandung, 2021)
This study aims to discuss the hadith regarding Aloe Vera. This research method is a qualitative type through literature and field studies with the takhrij and sharah hadith approaches. The results and discussion of this research is Aloe Vera which contains substances or compounds that are good for our health. The conclusion of this research is the takhrij and syarah of the Prophet SAW. about Aloe Vera plants with agrotechnology analysis which can be useful for body care as well as treating various diseases that exist in our bodies because the content of aloe vera is extraordinary.